Impaired parasympathetic augmentation under relaxation in patients with depression as assessed by a novel non-contact microwave radar system. (2nd January 2016) - Matsui, Takemi; Kakisaka, Kota; Shinba, Toshikazu
Abstract: In order to conduct objective screening of major depressive disorder (MDD), a chair-based system was developed which measures alteration of parasympathetic activation induced by relaxing audio-visual exposure in a non-contact way using dual compact-radars attached to a chair back. The system determines autonomic activation by calculating low (LF) and high frequency (HF) components of heart rate variability (HRV) before and after relaxation. Forty-one subjects (28 normal subjects, 13 MDD subjects) were exposed to relaxing natural sounds and images for 10 min. In order to determine the possibility of MDD from autonomic alteration induced by relaxing, linear discriminant analysis was conducted using LF and HF before and after relaxation. F -test revealed the significance of derived linear discriminant function ( p  < 0.001). The Mahalanobis distance and U value were 3.2 and 0.89, respectively. The derived linear discriminant function achieved 85% sensitivity (11 out of 13 MDD patients) and 89% specificity (25 out of 28 normal subjects).